Forecasting Oracle Performance - Shallahamer, Craig (Apress : Imprint: Apress, 2007)
What makes seasoned IT professionals run for cover? Answer: Forecasting Oracle Performance! Craig Shallahamer is an Oracle performance expert with over 18 years of experience. His book is the first to focus not on the problem of solving today's problem, but squarely on the problem of forecasting the future performance of an Oracle database. Other Oracle performance books are good for putting out fires; Craig's book helps you avoid all the heat in the first place. If you're an IT practioner who appreciates application over mathematical proofs than you'll be pleasantly surprised! Each chapter is filled with examples to transform the theory, mathematics, and methods into something you can practically apply. Craig's goal is to teach you about real-word Oracle performance forecasting. Period. There is no hidden agenda. This book is a kind of training course. After reading, studying, and practicing the material covered in this book, you to be able to confidently, responsibly, and professionally forecast performance and system capacity in a wide variety of real-life situations. If you are more management-minded (or want to be), you will be delighted with the service level management focus. Forecasting makes good business sense because it maximizes the return on IT investment and minimizes unplanned down time. To those who think forecasting is a waste of money: well...obviously, they've never been on the evening news because their company lost millions of dollars in revenue and brand destruction because of poorly performing or unavailable systems. Without a doubt, you will be equipped to deal with the realities of forecasting Oracle performance. But this book gives you more. Not only will you receive a technical and mathematical perspective, but also a communication, a presentation, and a management perspective. This is career building stuff and immensely satisfying!